Carbon footprint of inhalers in Brazil and Porto Alegre: impacts and alternatives. - Simões, Paola Flamia; Silva, Thamires Pereira Braga da; Barros, Enrique Falceto de; Patricio, Karina Pavão; Zandavalli, Rafaela Brugalli (My University, 2024)
The aim is to calculate the carbon footprint of metered-dose inhalers used for asthma and chronic obstructive pulmonary disease management, distributed by the Brazilian National Health Service in Brazil and in the city of Porto Alegre, Brazil, in the year 2019. Data regarding the dispensation of salbutamol and beclomethasone were obtained upon request from the Ministry of Health. The dispensations were multiplied by the proportional carbon footprint of each device. The prescription of the metered-dose inhalers resulted in between 24,889,141 and 60,878,728 tons of CO2-eq released into the atmosphere in Brazil (equivalent to traveling 23 to 57 million times the north-to-south distance of Brazil in a standard gasoline car); and between 459,830 and 1,151,008 tons of CO2-eq in the city of Porto Alegre. The study demonstrated the substantial amount of GreenHouse Gas emissions associated with these devices in Brazil. The substitution with dry powder inhalers or Soft mist inhalers in appropriate situations would prevent significant environmental harm, while also providing clinical benefits to patients, as they are currently the first-line choice recommended by clinical guidelines for the treatment of respiratory diseases.